Geometrical control of the magnetic anisotropy in six coordinate cobalt complexes. Issue 60 (26th June 2020) - Saber, Mohamed R.; Singh, Mukesh K.; Dunbar, Kim R.
Abstract : Combined experimental and ab initio calculations attribute the suppression of quantum tunneling and zero-field SMM behavior in the trigonal prismatic [CoTp py ]PF6 (2 ), evidenced by hysteresis up to 3 K, to the enforced rigidity and axial geometry. Abstract : The geometry of cobalt(ii ) ions in the axially distorted octahedral cation in [Co(MeCN)6 ](BF4 )2 (1 ) was compared to the trigonal prismatic cation in [CoTp py ]PF6 (2 ) which revealed significant differences in magnetic anisotropy. Combined experimental and ab initio CASSCF/NEVPT2 calculations support the observed zero field SMM behaviour for 2, with easy axis anisotropy, attributed to the rigidity of the trigonal prismatic ligand. Strong transverse anisotropy for 1 leads to significant quantum tunnelling processes.